The role of the ADAMTS13 cysteine-rich domain in VWF binding and proteolysis - de,Groot R; Lane,DA; Crawley,JTB (Blood, 2015)
ADAMTS13 proteolytically regulates the platelet-tethering function of von Willebrand factor (VWF). ADAMTS13 function is dependent upon multiple exosites that specifically bind the unraveled VWF A2 domain and enable proteolysis. We carried out a comprehensive functional analysis of the ADAMTS13 cysteine-rich (Cys-rich) domain using engineered glycans, sequence swaps, and single point mutations in this domain. Mutagenesis of Cys-rich domain–charged residues had no major effect on ADAMTS13 function, and 5 out of 6 engineered glycans on the Cys-rich domain also had no effect on ADAMTS13 function. However, a glycan attached at position 476 appreciably reduced both VWF binding and proteolysis. Substitution of Cys-rich sequences for the corresponding regions in ADAMTS1 identified a hydrophobic pocket involving residues Gly471-Val474 as being of critical importance for both VWF binding and proteolysis. Substitution of hydrophobic VWF A2 domain residues to serine in a region (residues 1642-1659) previously postulated to interact with the Cys-rich domain revealed the functional importance of VWF residues Ile1642, Trp1644, Ile1649, Leu1650, and Ile1651. Furthermore, the functional deficit of the ADAMTS13 Cys-rich Gly471-Val474 variant was dependent on these same hydrophobic VWF residues, suggesting that these regions form complementary binding sites that directly interact to enhance the efficiency of the proteolytic reaction.